THE EFFECT OF BRAND IMAGE ON PURCHASE DECISION THROUGH FEAR OF MISSING OUT (FOMO) ON THE PRODUCT MIE GACOAN IN THE CITY OF MAKASSAR - Muhammad Dzul Akbar; Tenri Sayu Puspitaningsih Dipoatmodjo; Muhammad Ilham Wardhana Haerudin; Muh. Ichwan Musa; Ilma Wulansari Hasdiansa (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to analyze the effect of Brand Image on Purchase Decision with Fear of Missing Out (FoMO) as a mediating variable for Mie Gacoan products in Makassar City. This research applied a quantitative method by distributing questionnaires to 202 respondents. The collected data were analyzed using Partial  Least Square (PLS). The results show that Brand Image has a positive and significant effect on both Fear of Missing Out and Purchase Decision. Additionally, Fear of Missing Out positively influences Purchase Decision. The study also confirms that Brand Image indirectly affects Purchase Decision through Fear of Missing Out as a mediating variable. This research concludes that Brand Image and FoMO play an essential role in influencing consumer purchasing decisions, particularly among young consumers who are actively engaged on social media.